Anxiety sensitivity and acculturative stress: Concurrent relations to mental health among Spanish-speaking Latinx in primary care. (December 2021) - Zvolensky, Michael J.; Bakhshaie, Jafar; Shepherd, Justin M.; Peraza, Natalia; Viana, Andres G.; Walker, Rheeda L.; Garza, Monica; Ochoa-Perez, Melissa; Lemaire, Chad
The Latinx population suffers from mental health inequalities. Although past work has implicated acculturative stress and anxiety sensitivity as important individual difference factors for anxiety and depression in this group, it is presently unclear how they work together to influence more severe anxiety and depressive symptom expression among Latinx. To help address this gap in the existing literature, the current study evaluated the role of concurrent anxiety sensitivity and acculturative stress, in terms of anxiety and depressive symptoms and disorders, in a Latinx population in a primary care setting. Participants included 142 Latinx individuals (86.7% female; Mage  = 39.66, SD  = 11.34). After accounting for shared variance, the results indicated that both anxiety sensitivity and acculturative stress were significantly associated with anxious arousal symptoms, social anxiety, and depressive symptoms. However, anxiety sensitivity, but not acculturative stress, was significantly related to a number of mood and anxiety disorders. These findings suggest the importance of assessing both anxiety sensitivity and acculturative stress in routine mental health screening, as both factors may be related to poorer psychological health among this group.